Strategic ICT-Use Intensity of Manufacturing Companies in Nigeria - Olamade, Olumuyiwa O; Oyebisi, Timothy O; Olabode, Samuel O (Journal of Asian Business Strategy, 2014)
ICT is strategic to a firm if it helps to gain a competitive advantage and or reduce a competitive disadvantage. The intensity of ICT application in shaping or sustaining strategy will depend on the competition faced by companies, their strategic response to the competition, and their capability to dynamically integrate ICT and competitive strategies. Based on a sample of manufacturing firms, three questions were formulated to determine if manufacturing companies in Nigeria strategically deploy ICT and the intensity of the deployment. The evidence produced by our analysis found support for the strategic use of ICT by the companies. We conclude that companies will be using ICT more strategically if competition is driven by the competitive advantages that are more ICT intensive.